2022
DOI: 10.1186/s13005-022-00310-9
|View full text |Cite
|
Sign up to set email alerts
|

Orbital volume changes during growth and development in human children assessed using cone beam computed tomography

Abstract: Objectives To measure growth-related changes in orbital volume from childhood to the late teenage years using cone-beam computed tomography (CBCT) scans. Methods This retrospective cohort study involved 65 (24 male, 41 female) healthy Caucasian children (ages 6–18 years) with existing serial craniofacial CBCT scans. CBCT scans were available for 292 orbits. Each orbit was transformed into a closed space with well-defined boundaries, and orbital vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…11,25 Given the physiologic growth of orbital volume with increasing age, pediatric abscess volumes intuitively are smaller than those of adolescent and adult abscesses. 20 The authors found mean OA volume to be significantly larger than SPA volume in an age-controlled comparison. OA volume ranged from 0.72 to 142.0 cm 3 while SPA volume ranged from 0.10 to 63.8 cm 3 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…11,25 Given the physiologic growth of orbital volume with increasing age, pediatric abscess volumes intuitively are smaller than those of adolescent and adult abscesses. 20 The authors found mean OA volume to be significantly larger than SPA volume in an age-controlled comparison. OA volume ranged from 0.72 to 142.0 cm 3 while SPA volume ranged from 0.10 to 63.8 cm 3 .…”
Section: Discussionmentioning
confidence: 88%
“…Given the association between age and orbital volume, a nonparametric regression was used to compare abscess volume between groups and control for age at presentation. 20 Traditional guidelines for surgical intervention in SPA management also vary by age, warranting a multiple logistic regression model to control for age at presentation when surgical intervention rate was compared between groups. 21 An α of 0.05 indicated statistical significance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Bentley et al (2002) estimated a model of agerelated changes in orbital volume in children from 0 to 15 years old and observed a linear growth rate of orbital volume throughout the age range studied, contradicting earlier models that tended to emphasize a growth curve of exponential decay, with a 77% of the total volume attained at five years. Also, a caucasian sample of children between 6-18 years shows an increase of the orbital volume in 1-2% per year throughout childhood until the late teens (Smith, 2020). Such differences in the pattern of growth of the orbital capsule may be accounted for by the measuring methods and sample composition used in each case.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort with these anomalies, we saw that older orbits did not grow anymore after the age of 6.5, in contrast to the changes seen in younger subjects, especially when 3D‐printed conformer therapy was started before the age of 1. Some studies suggest the orbit stops growing at age 5–6, others show a 1%–2% volume increase per year through late adolescence years, and again others have shown that orbital growth is not linear but sinusoid with fast and slow phases (Farkas et al., 1992; Smith et al., 2022; Waitzman et al., 1992; Wei et al., 2017; Zhang et al., 2022).…”
Section: Discussionmentioning
confidence: 99%